2018
DOI: 10.1159/000493138
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Vitamin D3 (Calcitriol) Serum Concentrations with Vitamin B12 and Folic Acid in Women Undergoing in vitro Fertilisation/Intracytoplasmatic Sperm Injection

Abstract: Background: The important role of vitamin D3 in human health is well recognized. In this study, we measured serum concentrations of vitamin D3, vitamin B12 and B9 (folic acid) in 410 women undergoing in vitro fertilisation (IVF)/intracytoplasmatic sperm injection (ICSI) with dedicated focus on 3-month changes in consideration of patients’ BMI. Methods: Patients were of European origin and did not take any supplementation of D3. In preparing for pregnancy, patients took ≥4 weeks 400 µg folic acid combined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
4
8
0
1
Order By: Relevance
“…Our data are in line with several in vitro and in vivo studies reporting seasonal dynamic of D3 and the impact on AMH [1]. However, our ndings show a parallel 3-month dynamic as AMH with peak levels of both, D3 and AMH delayed from August to end of October, supporting the hypothesis of our pilot study suggesting a prolonged tissue storage with a following slow release of D3 [36]. Here, in addition, a similar quartile dynamic was found in the ART outcome with best results from August to end of October.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our data are in line with several in vitro and in vivo studies reporting seasonal dynamic of D3 and the impact on AMH [1]. However, our ndings show a parallel 3-month dynamic as AMH with peak levels of both, D3 and AMH delayed from August to end of October, supporting the hypothesis of our pilot study suggesting a prolonged tissue storage with a following slow release of D3 [36]. Here, in addition, a similar quartile dynamic was found in the ART outcome with best results from August to end of October.…”
Section: Discussionsupporting
confidence: 92%
“…We could con rm and amend the results of our pilot study by Rogenhofer et al [36] showing statistically signi cant 3-month quartile changes of D3 serum concentrations (p < 0.0001) registering the maximum level from 1st August to 31th October with a mean of 27.7 mg/dl. The lowest expression was noted from 1st February to 30th April with a mean of 20.9 mg/dl (Fig.…”
Section: Vitamin D Dynamicsupporting
confidence: 60%
See 1 more Smart Citation
“…In a study of middle-aged women, vitamin D and vitamin B12 levels were reported to be related independent from fat mass of individuals (29). In a study by Rogenhofer et al, a high correlation between vitamin D levels and vitamin B12 levels was reported (30).…”
Section: Biochemical Resultsmentioning
confidence: 95%
“…Наукові дослідження вчених Університету Торонто показали, що у жінок з передменструальними симптомами, які відчувають до 95% жінок, недостатній рівень 25(OH)D може бути пов'язаний з їх тяжкістю [5,6]. Результати низки досліджень, проведених в Україні, свідчать, що нестачу та дефіцит вітаміну D реєструють більш ніж у 80% дорослого населення і лише у 6-7% жінок різного віку виявляють нормальний рівень вітаміну D [7]. Виділяють ряд захворювань, пов'язаних з недостатністю вітаміну D, які дуже впливають на здоров'я і якість життя жінки.…”
unclassified